2023
DOI: 10.3390/land12061260
|View full text |Cite
|
Sign up to set email alerts
|

Which Spatial Elements Influence Waterfront Space Vitality the Most?—A Comparative Tracking Study of the Maozhou River Renewal Project in Shenzhen, China

Abstract: Urban waterfront renewal, especially public space improvement, is important for regaining waterfront space vitality. However, existing studies constrained by sparse and hard-to-access data are hard to explore how changes in spatial elements during waterfront renewal would affect space vitality. Waterfront space vitality comprises social vitality represented by public behaviors and economic vitality represented by urban functional facilities. Taking the Maozhou River renewal project in China as an example, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Interestingly, it was found that waterfront spaces with a high degree of openness were not only detrimental to the promotion of positive emotions, but also had the potential to trigger negative emotions. While some studies have shown that high openness of the shoreline could stimulate visual sensations, and enhance the space's vitality, which provides a reason to linger, there is no direct evidence of its effect on emotional benefits [53][54][55]. However, there are still related studies that showed similar results.…”
Section: Effects Of Different Wlcs On Ebsmentioning
confidence: 99%
“…Interestingly, it was found that waterfront spaces with a high degree of openness were not only detrimental to the promotion of positive emotions, but also had the potential to trigger negative emotions. While some studies have shown that high openness of the shoreline could stimulate visual sensations, and enhance the space's vitality, which provides a reason to linger, there is no direct evidence of its effect on emotional benefits [53][54][55]. However, there are still related studies that showed similar results.…”
Section: Effects Of Different Wlcs On Ebsmentioning
confidence: 99%
“…The availability of leisure time plays a role in the duration of recreational sports activities along the urban riverfront (Gargiulo et al, 2020). Two other studies concluded that visitors extend their stays slightly on weekends compared to weekdays (Chen et al, 2022;Fan et al, 2023). Higher socioeconomic status households may allocate more leisure time to riverside activities, while renters and temporary residents, engrossed in their livelihoods, may have limited time by the riverside (Haeffner et al, 2017).…”
Section: Personal Attributesmentioning
confidence: 99%
“…While these assessments have traditionally relied on surveys and researcher self-evaluation, the advent of modern technologies, such as sensors and aerial imagery, has facilitated the creation of expansive databases. These databases enable a comprehensive insight into the factors influencing urban vitality, which encompass space morphology, community activities, urban events, and other factors [2].…”
Section: Introductionmentioning
confidence: 99%